2013
DOI: 10.1007/jhep03(2013)089
|View full text |Cite
|
Sign up to set email alerts
|

Kaon mixing beyond the SM from Nf = 2 tmQCD and model independent constraints from the UTA

Abstract: We present the first unquenched, continuum limit, lattice QCD results for the matrix elements of the operators describing neutral kaon oscillations in extensions of the Standard Model. Owing to the accuracy of our calculation on ∆S = 2 weak Hamiltonian matrix elements, we are able to provide a refined Unitarity Triangle analysis improving the bounds coming from model independent constraints on New Physics. In our nonperturbative computation we use a combination of N f = 2 maximally twisted sea quarks and Oster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 44 publications
(125 reference statements)
3
81
1
1
Order By: Relevance
“…These expressions have to be compared to the bounds from K-mixing taken from ref. [55] (Im) and ref. [56] (Re), and the bounds from B-mixing taken from ref.…”
Section: Constraints From ∆F = 2 Observablesmentioning
confidence: 88%
“…These expressions have to be compared to the bounds from K-mixing taken from ref. [55] (Im) and ref. [56] (Re), and the bounds from B-mixing taken from ref.…”
Section: Constraints From ∆F = 2 Observablesmentioning
confidence: 88%
“…Previous studies have shown that these ratios are large (∼ O(10)) as the BSM matrix elements are enhanced compared to the SM one [16,26,27] (this is expected from Chiral Perturbation Theory: the SM matrix element vanishes in the chiral limit whereas the BSM matrix elements remain finite). An advantage of this method compared to the bag parameters is that the denominators do not depend on the quark masses.…”
Section: The Ratios R Imentioning
confidence: 98%
“…The first computation performed with dynamical fermions was reported by our collaboration in [15] and was done with n f = 2 + 1 DW fermions at a single lattice spacing. It was followed by a n f = 2 computation by the European Twisted Mass (ETM) collaboration using twisted-mass Wilson fermions with several lattice spacings [16]. These two computations reported results in decent agreement (the matrix elements of O 2,3,4 agree within errors, O 5 only within ∼ 2 σ), suggesting that these quantities are not very sensitive to the number of flavours.…”
Section: Jhep11(2016)001mentioning
confidence: 99%
“…Using renormalization group equations, the Wilson coefficients can be evolved down to hadronic scales, where lattice evaluations of the matrix elements of the operators in (9) are given [64][65][66][67]. The presence of a dynamical gluino below mq does not change the anomalous dimensions of the operators at leading order (LO) [68][69][70][71].…”
Section: Meson Oscillationsmentioning
confidence: 99%